2024
DOI: 10.1002/nano.202300166
|View full text |Cite
|
Sign up to set email alerts
|

Pt‐Fe loaded nanostructured silicon and improvement of the magnetic performance

Petra Granitzer,
Klemens Rumpf,
Roberto Gonzalez‐Rodriguez
et al.

Abstract: This work reports the pore‐filling of porous silicon (PSi) and the loading of silicon nanotubes (SiNTs) with Pt‐Fe nanoparticles (NPs) and the corresponding different magnetic behavior of the two composite systems. The fabrication of magnetic hard/soft nanostructures is in demand for the purpose of achieving both a high energy product as well as the replacement of rare earth permanent magnets. Pt‐Fe templated by PSi shows a higher coercivity and remanence than SiNTs/Pt‐Fe and thus a higher hard magnetic perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The delivery and transfection of RNA to HeLa cells was shown to be ∼50%, demonstrating that porous silicon nanotubes have potential in nanomedicine for therapeutic applications. In a related study, Coffer and colleagues also demonstrated the porefilling of porous silicon and the loading of silicon nanotubes with Pt-Fe nanoparticles, demonstrating their corresponding different magnetic behavior of the fabricated systems [25].…”
Section: Areas Covered In the Special Topicmentioning
confidence: 96%
“…The delivery and transfection of RNA to HeLa cells was shown to be ∼50%, demonstrating that porous silicon nanotubes have potential in nanomedicine for therapeutic applications. In a related study, Coffer and colleagues also demonstrated the porefilling of porous silicon and the loading of silicon nanotubes with Pt-Fe nanoparticles, demonstrating their corresponding different magnetic behavior of the fabricated systems [25].…”
Section: Areas Covered In the Special Topicmentioning
confidence: 96%